2020
DOI: 10.1016/j.jalz.2019.09.086
|View full text |Cite
|
Sign up to set email alerts
|

Association between alcohol consumption and Alzheimer's disease: A Mendelian randomization study

Abstract: Introduction:Observational studies have suggested that light-to-moderate alcohol

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…For instance, a recent study of this type found no causal association between alcohol consumption and Alzheimer’s disease. 66 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study of this type found no causal association between alcohol consumption and Alzheimer’s disease. 66 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, drinking habits might alter the course of AD negatively (16). In addition, there is ample evidence of a causal association between alcohol consumption and an earlier Alzheimer's disease age of onset survival (AAOS) and increased γ-glutamyl transferase blood concentrations (17). Although modest alcohol consumption (≤12.5 g/day) is associated with a reduced risk of dementia, with 6 g/day of alcohol conferring a lower risk than other levels, excessive drinking (≥38 g/day) may instead elevate the risk (18).…”
Section: Resultsmentioning
confidence: 99%
“…Nondrinkers who were carriers for APOE4 showed a quicker decline in memory than controls 112 . Contradictory studies showed alcohol consumption of all levels was associated with more atrophy of the hippocampus 113 and an earlier age of AD onset 114 . A level above 48 g/day was also associated with reduced hippocampal volume 115 …”
Section: Modifiable Risk Factors Of Admentioning
confidence: 99%